Tantangan Dan Peluang Pendidikan Agama Islam Dalam Menghadapi Kenakalan Remaja Era Digital Di SMP Negeri 2 Sangatta Utara. - Sevia Rahayu Nur habibah; Moh Ibnu Faruk Fauzi; Eka Widyanti (Civiliza Publishing, Indonesia., 2026)
This study aims to describe juvenile delinquency in the digital era and identify the challenges and opportunities of Islamic Religious Education in dealing with juvenile delinquency in SMP Negeri 2 Sangatta Utara. This study uses a descriptive qualitative approach with field research methods through observation, interviews, and documentation. The results of the study showed that juvenile delinquency that occurred included skipping school, excessive use of gadgets, cyberbullying, and lack of student discipline. The challenges of PAI are the low digital literacy of teachers, conventional learning methods, and the influence of the environment and student associations that are less supportive, while the opportunity lies in the use of digital media as a means of learning, the delivery of more attractive Islamic values, and cooperation between teachers, schools, and families in fostering students' morals.